KOMUNIKASI PARIWISATA KABUPATEN LIMAPULUH KOTA UNTUK MEMBENTUK CITRA PARIWISATA HALAL SETELAH DITETAPKANNYA PROVINSI SUMATERA BARAT SEBAGAI THE WORLD HALAL TOURISM AWARD 2016 - Suhendra, Nofri; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
A halal tourism is a new concept in tourism sector. It is not a treat for tourism industry that has been existed long before the halal tourism is created, but it is a complement and it will not be an obstacle for the advance of tourism industry. Even numbers of countries in Asia have worked on halal tourism such as, Malaysia, Thailand, Singapore, Korea, Japan, Taiwan, and China. These countries have worked on halal tourism which is supported by various facilities and services that is provided by the citizen, government, and the regional government who fulfilled the criteria as halal destination according to Islam. In this research, the researcher focused on the type of halal tourism in Kabupaten Lima Puluh Kota, the communication media, and to obtain information about segmentation of halal tourism and tourism communication strategy that had been done by Dinas Pariwisata Pemuda dan Olahraga Kabupaten Lima Puluh Kota. The method for the research was a qualitative descriptive with mapping approach that aimed to inform facts and data about the potential possessed by halal tourism, also tourism communication strategy used by Dinas Pariwisata Pemuda dan Olahraga Kabupaten Limapuluh Kota to develop the potential of halal tourism. The findings of this research were: (a) The type of halal tourism being developed is the developing of syariah hotel and restaurant, religion tourism, history, cultures and halal tourism objects such as Harau Valley, the Grassland of Padang Mengatas and Kapalo Banda, (b) The media used are website, Facebook, Twitter and Instagram, (c) The segmentation is divided into four types, these are geographical, demographic, psychographic and behaviour, (d) the communication strategy used to develop the halal tourism is communication marketing mix which resulted to form a society who is aware of tourism, joining the Ikatan Fotografi Indonesia (IFI), joining various events, set up their own events and using communication media in promoting process. Keyword : Tourism Communication, halal tourism, Kabupaten Limapuluh Kota